Human capital effects of one-on-one time with parents: Evidence from a Swedish childcare access reform - Anna Sjögren; Malin Tallås Ahlzén (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2022)
We study the effects of increased opportunities for one-on-one time with a parent during infancy on the human capital formation of children. To this end, we exploit a nationwide reform that mandated Swedish municipalities to offer childcare access for infants' older siblings, while parents were on parental leave to care for their infants. Survey data on childcare enrollment show that the reform had a significant impact on the childcare enrollment of older siblings. Using rich administrative data, we estimate intention-to-treat effects in a differences-in-differences setting, comparing infants with and without siblings of childcare age, pre- and post-reform, in municipalities that were affected the reform. We find no robust overall effects on the children's 6th grade test scores, but we find evidence of positive effects on test scores for sons of less than university educated mothers and daughters of highly educated mothers. Exploring potential pathways, we find no evidence of changes in quantity of parental time during infancy, pointing instead towards the role of improved quality of parent-child interactions as a result of less competition for parental time. We also find that improvements in physical and mental health in school age may have contributed to the positive effect for boys and a lower probability of having a younger sibling may have reduced competition for parental time further and contributed to the improved test scores for girls.
Keywords: I14; I21; J13; I14; I21; J13; 330; Human capital formation; Parental time investments; Cognitive development; Parental leave; Quasi-experiment